Level of blood lactate concentration after skiing on a 15 gate slalom course - Dolenec, A.; Tomazin, K.; Biaz, J.; Strojnik, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In alpine skiing, most of the required energy for Slalom skiing comes from an anaerobic glycolytic System (Andersen, Montgomery, 1988; Tesch, 1995). This causes the rapid onset of fatigue. Following a race, blood lactate concentration averages from 9 to13 mmol/l (Andersen, Montgomery, 1988), hence the fatigue is beyond the anaerobic threshold. Fatigue beyond anaerobic threshold disturbs the body's balance (Nardone et al., 1997), which results in a slowing of the learning process. The blood lactate concentration does not reach anaerobic threshold if the slalom course is shortened to 15 gates (Dolenec et al., 2006). Therefore, skiing on a 15 gate course with appropriate rests might be suitable for learning a skiing technique. The aim of this experiment is to find the level of blood lactate concentration that appears in slalom skiers on a 15 gates course with a five minute rest between runs.